Discussion on Fire-proof Sealing Technology and Product. (2016) - Sun, Zhuo-er; Zhou, Yang
Abstract: Fire-proof sealing and plugging in building is an important technical means of building fire protection as well as the emphasis and difficulty of current construction area. From the starting point of analysing the principle of fire-proof sealing and plugging in building and analysing some key influence factors, this paper originally proposes the composite applications of fire-proof sealing technical measures, on the basis of combining the engineering application. Then taking the new fire-proof sealing sheet for representative example, it introduces the current situation of fire-proof sealing product and gives reasons analysis. At last, it brings up corresponding suggestions from four aspects: the product quality, product standard, product selection and construction application, trying to provide some new thoughts and methods for solving fire-proof sealing and plugging problem.